Assessment of the functioning of quality monitoring system in steelwork based on the BOST method - Stanisław Borkowski; Piotr Sygut (Production Engineering Archives, 2015)
This chapter presents the research results on the functioning of the quality control system at the steelworks. The study was conducted using an innovative BOST method. Highlighted the need to improve processes visual inspection as a means of improving the quality of finished products. Based on a survey conducted among employees of the production factors have been identified which require improvement process in question.